A bibliometric analysis: Current status and frontier trends of Schwann cells in neurosciences - Wang, Yan; Zhang, Shiwen; Zhi, Jincao; Huang, Meiling; Pei, Fei (Frontiers in Molecular Neuroscience, 2023)
Background This review aims to present a comprehensive bibliometric analysis related to Schwann cells (SCs) in neurosciences from 2012 to 2021. Methods We used the Web of Science core collection database to obtain publications on SCs in the field of neurosciences from 2012 to 2021. The obtained data were further visually analyzed by using CiteSpace, VOSviewer, and an online bibliometric platform. Results We retrieved a total of 1,923 publications related to SCs in neurosciences. The number of publications in this field fluctuates steadily each year, and the number of citations is increasing year by year. The United States is leading the field, with LERU and the University OF London as influential institutions, Jessen KR and Feltri ML as the most representative authors, and GLIA and JOURNAL OF NEUROSCIENCE as authoritative journals in the field. Meanwhile, we predict that a more in-depth study of autophagy and phagocytosis functions of SCs and the key regulator c-Jun will probably be a hot spot for future research. Conclusion This study summarizes the current research results and predicts research trends for further research, which will facilitate researchers in quickly understanding the current state of research in the field while referring to new research directions.